2018
DOI: 10.1371/journal.pone.0203867
|View full text |Cite
|
Sign up to set email alerts
|

Are views towards egg farming associated with Brazilian and Chilean egg consumers’ purchasing habits?

Abstract: In many industrialised countries, public rejection of intensive animal production systems has led to the development of legislation and industry actions that have resulted in significant changes in animal care at the farm level. However, little is known about the views of citizens from emerging countries regarding animal production. The aims of this study were to explore the views of Brazilian and Chilean consumers towards egg farming, and to investigate if these views are associated with participants’ eggs pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 42 publications
(69 reference statements)
4
16
0
2
Order By: Relevance
“…The fact that the majority of participants supported the use of antibiotics and rejected the consumption of meat from animals housed in “hospital pens” is in line with those describing that the most appropriate solution for unhealthy pigs would be to make all efforts to recover the animal, including giving antibiotics, but not using them for food production. This seems to indicate consumers’ concerns regarding animal welfare, which is in accordance with previous studies showing that the general public has become increasingly interested in farm animal welfare and aspects of food animal production, both in developed [ 11 , 44 ] and developing nations [ 5 , 8 , 45 , 46 ]. Lay citizens believe that animals are sentient beings with capacity to suffer and have positive emotional states [ 47 ], and that to impose pain on animals is unacceptable [ 48 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The fact that the majority of participants supported the use of antibiotics and rejected the consumption of meat from animals housed in “hospital pens” is in line with those describing that the most appropriate solution for unhealthy pigs would be to make all efforts to recover the animal, including giving antibiotics, but not using them for food production. This seems to indicate consumers’ concerns regarding animal welfare, which is in accordance with previous studies showing that the general public has become increasingly interested in farm animal welfare and aspects of food animal production, both in developed [ 11 , 44 ] and developing nations [ 5 , 8 , 45 , 46 ]. Lay citizens believe that animals are sentient beings with capacity to suffer and have positive emotional states [ 47 ], and that to impose pain on animals is unacceptable [ 48 ].…”
Section: Discussionsupporting
confidence: 89%
“…Most consumers eat food products from animals treated with antibiotics, but they may not be aware of this [ 20 ]. However, their confidence in the food production sector has been decreasing [ 51 ] and consumers have increasingly expressed concerns about residues in meat [ 52 ], especially hormones and veterinary drug residues [ 43 , 46 ]. Previous studies have already reported that consumers are willing to pay more for antibiotic-free animal products [ 20 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Swiss consumers would pay almost 32% more for organic eggs [45]. Teixeira et al [46] investigated emerging countries in terms of consumers' views on egg farming and purchasing habits. In Brazil and Chile, they found that egg consumers care the most for animal welfare, and more than half of them are willing to pay at least 5% more for eggs produced with animal-friendly methods.…”
Section: Consumers' Preference and Perception Of Organic Labelled Foodmentioning
confidence: 99%
“…Improving animal welfare is the key to improving bird health, quality of life and productivity [2]. A diet of mealworms and fresh grass contribute to improve gait score, chicken meat quality, produce higher platelet values and richer intestinal microorganisms in free-range environment [22]. Free-range environment can improve egg laying performance, promote feeding activities of chickens, and improve animal welfare.…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%